2013
DOI: 10.1002/uog.12429
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis using combined quantitative fluorescent polymerase chain reaction and array comparative genomic hybridization analysis as a first‐line test: results from over 1000 consecutive cases

Abstract: Objectives First, to assess the performance of a prenatal diagnostic service using quantitative fluorescent polymerase chain reaction (QF-PCR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 26 publications
5
50
3
Order By: Relevance
“…While pregnancies found to have increased NT/nuchal fold or cystic hygroma had the highest rate of aneuploidy (30.9%), we did not detect any microdeletions or microduplications in this group. Some reports suggest that this ultrasound abnormality is not associated with an increased risk for submicroscopic chromosome abnormalities [30,[32][33][34] , but other studies have found such abnormalities using microarrays or other molecular tests, including the identification of some of the syndromes on our panel, such as 22q11.21 microdeletions [29,[35][36][37] .…”
Section: Discussionmentioning
confidence: 79%
“…While pregnancies found to have increased NT/nuchal fold or cystic hygroma had the highest rate of aneuploidy (30.9%), we did not detect any microdeletions or microduplications in this group. Some reports suggest that this ultrasound abnormality is not associated with an increased risk for submicroscopic chromosome abnormalities [30,[32][33][34] , but other studies have found such abnormalities using microarrays or other molecular tests, including the identification of some of the syndromes on our panel, such as 22q11.21 microdeletions [29,[35][36][37] .…”
Section: Discussionmentioning
confidence: 79%
“…12 The results suggest that fetal anomalies on ultrasonography would be expected to be rare, consistent with the low prevalence of 15q13.3 deletions detected by prenatal chromosomal microarray studies. 11,23,24 Postnatal chromosomal microarray detection, perhaps secondary to referral for DD/ID, is higher. 9 By contrast, the most common large rare CNVs, 22q11.2 deletions, have high penetrance for both neuropsychiatric disorders and congenital anomalies, 25 and higher prenatal detection (0.29%) as compared with 15q13.3 deletions (0.02-0.09%).…”
Section: 5 Discussionmentioning
confidence: 99%
“…An increase in the prevalence of SL in affected pregnancies can also be observed in the data presented by Wapner et al (3.6 versus 0.8%) and by Scott et al (1.4 versus 0.55%). 7,37 If the phenotype of the SL involves a structural abnormality such as a heart anomaly in case of 1q21.1 duplication, an ultrasound investigation should be offered when the SL is encountered or when there is a family history of such a SL. Because of the higher prevalence of SL in fetuses with ultrasound abnormalities, it may seem to be defendable to offer a detailed second trimester ultrasound examination in all cases of SL or in families known to carry a SL.…”
Section: Rarity Of Particular Imbalances and Postnatal Biasmentioning
confidence: 99%